2019
DOI: 10.36346/sarjaf.2019.v01i02.003
|View full text |Cite
|
Sign up to set email alerts
|

Domination of Pollutant Residues among Food Products of South-East Asian Countries

Abstract: Southeast Asia is a region that produces high amounts of key food commodities and includes areas of divergent socioeconomic status. Food security is a high-priority issue for sustainable global development both quantitatively and qualitatively. In recent decades, adverse effects of unexpected contaminants on crop quality have threatened both food security and human health. Public concern about the adverse environmental and human health impacts of organochlorine contaminants led to strict regulations on their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A similar study says Bangladesh will exceed 35-degree Celsius before the end of the century [63] . Consuming arsenic contaminated food grains could be another reason of high diabetes prevalence [64] . In sex-stratified analyses with 641 subjects from rural Bangladesh, Paul et al, 2019 reported arsenic exposure (50.01-150 μg/L) showed a clearer pattern of dose-dependent risk for hyperglycemia in females than males [65] .…”
Section: Other Issues 61 Climate and Environmentmentioning
confidence: 99%
“…A similar study says Bangladesh will exceed 35-degree Celsius before the end of the century [63] . Consuming arsenic contaminated food grains could be another reason of high diabetes prevalence [64] . In sex-stratified analyses with 641 subjects from rural Bangladesh, Paul et al, 2019 reported arsenic exposure (50.01-150 μg/L) showed a clearer pattern of dose-dependent risk for hyperglycemia in females than males [65] .…”
Section: Other Issues 61 Climate and Environmentmentioning
confidence: 99%